Family communication dynamics: equilibrium with dialectical tension in "Turning Red" film - hanifah, Hanifah; Farady Marta, Rustono; Panggabean, Hana; Amanda, Mercedes (Jurnal Studi Komunikasi, 2023)
Turning red film shows us that there is regeneration in parenting style. This parenting style focuses on the successful event in life and achievement but does not see the emotional side of the child. The dynamics of family communication, as seen in the Turning Red film, were seen to be something important in parenting. The issue in family communication will create tension and reduce family harmony. Le Praire mentions that there are two types of family communication, which are nurturing and controlling. Communication is full of contrary expressions and tension between one another, which we call relational dialectical tension. With the family communication dynamics in the film Turning Red, the researcher tries to find the equilibrium in family communication. The researcher used Tzvetan Todorov’s narrative analysis. Todorov divides the analysis into five stages, starting from equilibrium until there is a new equilibrium. This research shows that the dialectical tension colouring the films is stability vs change and integration vs autonomy. Parents’ acceptance of their children in every aspect, including their developmental stage and emotional needs, will build a higher attachment.